Studi Deskriptif Permasalahan Pembelajaran PKn dalam Membentuk Karakter Siswa Kelas V SD 12 Kota Bengkulu - Andita, Resi; Djuwita, Puspa; Hasnawati, Hasnawati (UNIB Press, 2018)
This study aims to describe the learning of Civic learning in shaping the character of the students of grade V SD 12 Kota Bengkulu. The type of this research is descriptive qualitative naturalistic. The subjects of this research are teachers and students of grade V SD 12 Kota Bengkulu. The conclusions of this research are: (1) Teachers have not developed their own curriculum because they do not have time and do not understand the making of syllabus and RPP which is suitable with curriculum development. (2) Students do not understand the material given by the teacher because the teacher only uses lecture method and does not develop contextual based learning materials, the material only from the students' book makes the students pay less attention to the teacher when the learning takes place. (3) The size of the classroom does not fully support the learningactivities.